59 Associations of Biological Sex with Clinicopathologic Features of Cutaneous Melanoma. (19th August 2022) - Tay, T; Oudit, D; Cook, M; Green, AC
Abstract: Aim: It is commonly known that women have better prognosis than men after diagnosis of primary cutaneous melanoma. However, few studies have investigated whether histopathological prognostic factors are associated with this difference. This study aimed to investigate if there were sex-specific differences in prognostic features of primary melanoma at time of diagnosis in a large clinical series. Method: This was a records-based observational study of unselected patients treated for melanoma in a major tertiary oncology centre in the United Kingdoms, 2002–2016. Prognostic features (age at diagnosis; thickness of primary melanoma; ulceration and mitotic count) were extracted from histological reports and sex-specific differences tested for significance using X 2 test. Results: Among 1323 melanoma patients of median age 61 years (range 15–99), and roughly equal proportions of males (640, 48%) and females (683, 52%), females had significantly earlier age of presentation on average than males (58 vs 64 years) (p<0.001). Comparing Breslow thickness of <2mm vs ≥2mm, significantly more females (414, 67%) than males (282, 55%) had melanomas <2mm (p<0.001). Other key histopathological factors namely presence of ulceration (p=0.073) and mitotic rate (p=0.618) were not significantly different by sex. Conclusions: We found that female melanoma patients presented at an earlier age and with thinner primary melanomas than males, but mitotic rate (speed of tumour growth) was not significantly different. These data suggest that females' better prognosis is explained by their tendency to present earlier with suspicious skin lesions than males.